Mathematics as a tool to understand the Economy within the research perspective of the National University of San Marcos - Pino Romero, Neisser (2017)
Mathematics from its beginnings has tried to describe the reality in which one lives, over time has been supporting the different sciences of which with this formal and abstract support has been greatly strengthened over time generating mathematical models, formulas, expressions that Solve real problems as far as you can. For how much, that the economy where it is studied and analyzes the different phenomena that involve the dynamics of generation of goods and resources, services and processes in the market, reason why the economy has needed of the mathematics to formalize formally with formal expressions And abstract but with interpretations applied to reality.